HEALTH COMPLAINTS AMONG FISHERMEN AT THE FISHING PORT OF BANTEN PROVINCE - Pertiwi, Wiwik Eko; Annissa, Annissa; Eka Mathofani, Puji; Ernawati, Ernawati; Darmawan, Erwan (HEARTY, 2025)
Fishermen are a group of coastal communities and belong to a community that are still underdeveloped and in a marginalized position. Most fishermen live their daily lives and activities traditionally. The daily activities of fishermen and exposure to environmental factors cause fishermen to be at risk of various health problems, including dermatitis, complaints of pain in the lower back, hearing loss, visual impairment and complaints of barotrauma. This study aims to determine the description of complaints of health problems in fishermen. This research was conducted at the Port in the working area of Health Quarantine Center Region 1 of the Ministry of Health of Banten Province. The method used for data collection in this study used a descriptive approach with questionnaire instruments and interview methods. The research respondents were 96 fishermen who were taken based on the calculation of the Slovin formula. Sample determination based on accidental techniques. The results showed that more than 50% of respondents stated that they experienced health problems. Dermatitis complaints were 69.8%, Low Back Pain was 59.4%, hearing loss was 63.5%, visual impairment was 67.7%, and barotrauma complaints were 68.8%. These health complaints are felt by most fishermen and are thought to be caused by environmental factors, work positions and personal factors. Based on the results of the study, it is recommended to improve and develop cooperation with related units in terms of special health checks for fishermen.